1978
DOI: 10.1177/002224377801500111
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Content Analytic System for Analysis of Bargaining Communication in Marketing

Abstract: A content analytic system focused on marketing communications can provide important insights into bargaining behavior. This article concerns testing the reliability and assessing the validity of a theoretically based communication categorization scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(20 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…In answering the needs expressed by Angelmar and Ster (1978), we advance a theoretical model of con- A variety of managerial implications can be derived from the theoretical model. Initial salesperson efforts to qualify the consumer should include attempts to identify the consumer's operative product and/or negotiation knowledge, as it is likely to have a significant impact on outcome expectations and pursuant negotiation strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In answering the needs expressed by Angelmar and Ster (1978), we advance a theoretical model of con- A variety of managerial implications can be derived from the theoretical model. Initial salesperson efforts to qualify the consumer should include attempts to identify the consumer's operative product and/or negotiation knowledge, as it is likely to have a significant impact on outcome expectations and pursuant negotiation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The antecedent condition of perceived power and transaction relationship dependency has received considerable attention in the marketing channels literature (e.g., Angelmar and Ster 1978;Gaski 1984). Whereas negotiated transactions in a channel context are likely to be characterized by a variety of perceived/actual power distributions among channel participants, the retailer in a consumer negotiation context has a significant power advantage (through superior market and competitor information and a skilled sales staff) over the consumer (Dwyer 1984)…”
Section: Specific Antecedent Conditionsmentioning
confidence: 99%
“…This approach may be particularly effective for Cluster 3-the "compulsives"-who were significantly higher in materialism than all other groups. Angelmar and Stern (1978) suggested that bargaining may be the " ... central element of marketing transactions in a number of contexts" (p. 100). As described by Evans and Beltramini (1987), when pricing products such as autos, homes, and appliances, negotiations may occur.…”
Section: Future Research Issuesmentioning
confidence: 99%
“…Bargaining Strutegus can be viewed as falling along a representational/ instrumental continuum (Angelmar and Stem, 1978).…”
Section: Process Variablesmentioning
confidence: 99%